From job crafting to home crafting and back again: A shortitudinal study on the spillover between job and home crafting - Verena C. Haun; Lina Marie Mülder; Anna-Laura Schmitz (Journal of Occupational and Organizational Psychology, 2022)
Building on the notion that successful crafting in one life domain spills over into another domain, we investigated the reciprocal effects between job and home crafting in 134 workers, using a shortitudinal study with a two-week time lag. The results of cross-lagged panel analyses suggested that there were reciprocal effects between the work and home domains of the crafting dimensions of increasing structural resources and reducing hindering social demands. Increasing social job resources lead to increasing social home resources, but the reverse is not true. No cross-lagged effects were found for increasing challenging demands and reducing hindering structural job demands at work and home.
Keywords: 650; home crafting; job crafting; proactivity; spillover